Malaysia-Thailand Cross Border Trade and Cross Border Special Economic Zone Potential: A Case Study of Rantau Panjang Sungai Kolok Cross Border Town - Anuar, Abdul Rahim; Harun, Azhar (Universiti Utara Malaysia Press, 2018)
Towns along the Malaysia-Thailand border have always been associated with backwardness and being low-income regions. This is mainly because policy development in these border regions is based more on defence and security rather than economic considerations. Economic structures and cross-border trade towns of Sg. Kolok (Narathiwat, Southern Thailand) and Rantau Panjang (Kelantan, Malaysia) were examined with the objective to measure cross-border economic activity and the feasibility of establishing a Cross Border Special Economic Zone. Both towns are a shopping haven among local and foreign tourists and have the potential to become a leading cross-border tourism product of the Malaysia-Thailand border. The Malaysian government has also implemented the Eastern Corridor Economic Region to develop the East Coast region including Kelantan. Meanwhile, the Thailand Government has carried out the Southern Border Provinces Special Zone to develop its Southern region, including Narathiwat. With the security assurance in Southern Thailand coupled with both development plans being implemented, this may intensify economic activities in the towns of Rantau Panjang and Sg. Kolok. It was revealed that this has a spill-over effect in the border areas and the potential of creating a Cross Border Special Economic Zone at these border towns.